2016
DOI: 10.1680/jgele.16.00073
|View full text |Cite
|
Sign up to set email alerts
|

System to measure three-dimensional movements in physical models

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. used to capture images of a deforming soil surface. The images were used to reconstruct the observed scene to a high density, accurate 3D point cloud. A new method has been developed to process the obtained 3D point clouds and images to determine 3D displacement vectors. The procedure is highly automatic which allows large data sets to be processed with minimal manual intervention. Two series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The effect of camera resolution seems to be not significant to the measurement precision as IPhone 6s (12Mega-pixel) and DSLR Canon (18Mega-pixel) yielded similar precisions which are in line with the results reported by Galland et al (2016) and Le et al (2016). It can be seen that camera resolution is not the only factor that governs the quality of images and hence the quality of 3D point clouds.…”
Section: Region Of Interestsupporting
confidence: 82%
See 4 more Smart Citations
“…The effect of camera resolution seems to be not significant to the measurement precision as IPhone 6s (12Mega-pixel) and DSLR Canon (18Mega-pixel) yielded similar precisions which are in line with the results reported by Galland et al (2016) and Le et al (2016). It can be seen that camera resolution is not the only factor that governs the quality of images and hence the quality of 3D point clouds.…”
Section: Region Of Interestsupporting
confidence: 82%
“…Galland et al (2016) used Micmac to analyse four images taken by 24 Mega-Pixel cameras and the achieved measurement precision was 50µm. Similarly, Le et al (2016) reported a precision of 50µm was achieved by using Micmac to analyse three images, taken by three 2Mega-pixel cameras.…”
Section: Review On Sfm-mvs Technique and Micmac Softwarementioning
confidence: 96%
See 3 more Smart Citations